PENGARUH PROMOSI DAN KUALITAS PRODUK ALAT KESEHATAN TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN PADA PT. HARSONS MEDICALINDO TRADING - Suci Minzathu; Muh Akob; Akhmad Muhammadin (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2026)
This study aims to test and analyze the influence of Promotion and Quality of Medical Device Products on Consumer Loyalty through Consumer Satisfaction at PT. Harsons Medicalido Trading. Data collection uses primary data with a questionnaire technique whose samples were obtained from consumers of medical devices with a random sampling system totaling 70 consumers. The results of the questionnaire have been tested using SPSS Version 26 software with instrument testing, classical assumptions and path analysis. Based on the results of the analysis, this study proves that be hypotheses are accepted and rejected, namely the first hypothesis Promotion has no effect and is not significant on consumer satisfaction. Second, Product quality has an effect and is significant on consumer satisfaction. Third, Consumer satisfaction has an effect and is significant on consumer loyalty. Fourth, Promotion has an effect and is significant on consumer loyalty. Fifth, Product quality has no effect and is not significant on consumer loyalty. Sixth, Promotion has no effect and is not significant on consumer loyalty through consumer satisfaction and Seventh, Product quality has no effect and is not significant on consumer loyalty through consumer satisfaction.